The Tuberin and Cyclin B1 complex functions as a novel G2/M sensor of serum conditions and Akt signaling - Fidalgo da Silva, Elizabeth (PLoS One, 2019)
A great deal of ground breaking work has determined that the Tuberin and Hamartin Complex function as a negative regulator of protein synthesis and cell cycle progression through G1/S. This is largely attributed to the GTPase activity of Tuberin that indirectly inhibits the mammalian target of rapamycin (mTOR). During times of ample nutrition Tuberin is inhibited by growth factor signaling, including direct phosphorylation by Akt/PKB, allowing for activation of mTOR and subsequent protein synthesis. It is well rationalized that maintaining homeostasis requires communication between cell growth (mTOR signaling) and cell division (cell cycle regulation), however how this occurs mechanistically has not been resolved. This work demonstrates that in the presence of high serum, and/or Akt signaling, direct binding between Tuberin and the G2/M cyclin, Cyclin B1, is stabilized and the rate of mitotic entry is decreased. Importantly, we show that this results in an increase in cell size. We propose that this represents a novel cell cycle checkpoint linking mitotic onset with the nutritional status of the cell to control cell growth.